Local knowledge, pattern and diversity of use of Sclerocarya birrea - Assogbadjo Achille E; Lykke Anne; Gouwakinnou Gerard N; Sinsin Brice (BMC, 2011)
Abstract Background Growing interest is on food tree species in general, and particularly indigenous fruit tree species in developing countries since they are inherent to most tropical landscapes and serve the dual function of local livelihood support and biodiversity conservation. It is therefore relevant to assess the level of integration of these species in local cultures and the factors affecting them. This study aims at assessing knowledge and uses of Sclerocarya birrea subsp. birrea and factors affecting the use values within and between communities. Methods This study combines quantitative and qualitative ethnobotanical approaches to investigate uses and factors affecting the use value of S. birrea subsp. birrea. Nine group discussions as well as 161 individual interviews were held in the dry and typical Sudanian zones. Seven different ethnic groups were involved and the survey focused on local uses and perception of factors affecting the dynamics of S. birrea. Results The species has a multitude of uses; all organs are used for more than 20 different purposes. The study highlights how gender, local availability, ethnicity and community location interact to influence the utilization value of the species. People living in drier areas with high occurrence of the S. birrea use it more than those living in wetter areas with low occurrence. While domestic and subsistence uses do not appear to threaten the species, carving, clearing and drought stand out as the major causes of its decline. Conclusions Many factors and their interactions influence the use pattern of the species within and between communities. When compared to the level of exploitation of S. birrea subsp. caffra in southern Africa, the subspecies birrea is at this point relatively underutilized. A high commercial potential exists due to its simple propagation ability and makes it an interesting agroforestry resource.